Volunteering and Ages: Observations from the youth, adult and old age volunteers in Santiago - Sepúlveda Miranda, Nelson; Muñoz Mayne-Nicholls, Antonio (MAD, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Volunteering, understood as a manifestation of the collaboration, is constructed from the observers to describe and explain the reality. In this sense, this text addresses to the most common communication on volunteering, as identified by youth, adults and elderly volunteers from the city of Santiago de Chile, who built their own ages when they produce collaborative communications.